2016
DOI: 10.1038/srep30609
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biglycan gene expression in the adipose tissues of obese women and its association with obesity-related genes and metabolic parameters

Abstract: Extracellular matrix (ECM) remodeling dynamically occurs to accommodate adipose tissue expansion during obesity. One non-fibrillar component of ECM, biglycan, is released from the matrix in response to tissue stress; the soluble form of biglycan binds to toll-like receptor 2/4 on macrophages, causing proinflammatory cytokine secretion. To investigate the pattern and regulatory properties of biglycan expression in human adipose tissues in the context of obesity and its related diseases, we recruited 21 non-diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The validation of RGs for normalization needs to be considered in the experimental design of studies based on qPCR. Despite β-actin being often employed as the sole reference gene for RT-qPCR data normalization 14 , 48 50 , our current study showed that β-actin was one of the most unstable genes in almost all the models assessed. Our data are in agreement with a recent study from Li et al .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The validation of RGs for normalization needs to be considered in the experimental design of studies based on qPCR. Despite β-actin being often employed as the sole reference gene for RT-qPCR data normalization 14 , 48 50 , our current study showed that β-actin was one of the most unstable genes in almost all the models assessed. Our data are in agreement with a recent study from Li et al .…”
Section: Discussionmentioning
confidence: 52%
“…Despite the growing need for increased accuracy and reliability of data generated using RT-qPCR, commonly used RGs are still employed without further validation, or have been found to be unstable in different tissues and physiological conditions 14 – 16 . Thus, the current study aimed to identify suitable RGs to perform quantitative transcriptomic analysis based on RT-qPCR for obesity and diabetes research, employing in vitro models, mouse models and human tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…Although biglycan is present in adipose tissue in the obese state, its action is poorly understood [14,34]. Pathway enrichment analysis of the differentially expressed genes in the liver tissue between Bgn 0/− and WT mice indicate alterations in numerous metabolic related pathways, including metabolism of lipid and lipoprotein, metabolism of amino acids and derivatives, and fundamental cell metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Biglycan has also been related with low grade inflammatory state in obesity and type 2 diabetes and development of insulin resistance [13,14]. More recently, biglycan has been associated with a broad range of neurode-generative events and disorders such as amyloid metabolism in Alzheimer’s disease pathology [15], inhibition of neurite outgrowth in sensory neurons [16], and neocortical neuronal survival [12,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Adipocyte size was estimated using the mean cross-sectional area of adipocytes in hematoxylin and eosin (H&E)-stained sections of adipose tissue, as previously described 31 . Paired samples of VAT and SAT were obtained from a subgroup of subjects.…”
Section: Methodsmentioning
confidence: 99%